2020
DOI: 10.3390/ijerph17186794
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Mental Health Due to COVID-19 Pandemic: Cross-Sectional Study in Portugal and Brazil

Abstract: Mental health effects secondary to the COVID-19 pandemic were till recently considered less important or were neglected. Portugal and Brazil are facing the pandemic in quite different ways. This study aimed to describe the mental health status of the general adult population in Portugal and Brazil during the COVID-19 pandemic and analyze the differences between the two countries. A cross-sectional quantitative study was based on an online questionnaire. Socio-demographic data were collected in addition to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
109
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 51 publications
11
109
2
13
Order By: Relevance
“…In the present study, being a female healthcare worker was a predictor of higher levels of both coronavirus-related anxiety and fear of COVID-19. This result is in agreement with recently published studies conducted in the general population of several countries [ 46 , 47 , 48 ], including Portugal [ 5 ]. In these studies, the female gender was found to be more vulnerable psychologically than males during the COVID-19 pandemic, with a higher prevalence of anxiety and/or fear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, being a female healthcare worker was a predictor of higher levels of both coronavirus-related anxiety and fear of COVID-19. This result is in agreement with recently published studies conducted in the general population of several countries [ 46 , 47 , 48 ], including Portugal [ 5 ]. In these studies, the female gender was found to be more vulnerable psychologically than males during the COVID-19 pandemic, with a higher prevalence of anxiety and/or fear.…”
Section: Discussionsupporting
confidence: 93%
“…It is recognized that the aforementioned pandemic has negatively affected the mental health of the general population [ 5 ]. For healthcare workers, it was not different.…”
Section: Introductionmentioning
confidence: 99%
“…There is no clear evidence about the predictor factors of the psychological impact of quarantine. The results of a study carried out on the Portuguese and Brazilian populations suggested that sociodemographic factors such as being female, having a higher educational level, being a student, living with family members or a partner in the period of social isolation or low levels of depression were significantly associated with increased levels of life satisfaction scores [44]. However, in another study, age, marital status, educational level, co-living status, or having children were not significantly associated with this psychological data [45].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that due to the ongoing COVID-19 pandemic, people are experiencing high levels of stress, depression, and anxiety, as well as levels of post-traumatic stress that are above the cut-off for post-traumatic stress disorder (PTSD) [5][6][7]. Healthcare professionals who come in close contact with COVID-19 patients are deeply affected by this novel virus and experience mental health challenges, including stress, depression, anxiety, PTSD, and burnout [8][9][10][11][12][13], which can have deleterious effects on their quality of life [11] and increase their turnover intention [14].…”
Section: Introductionmentioning
confidence: 99%